2002
DOI: 10.1046/j.1532-5415.2002.50019.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Vision Function Related to Physical Functional Ability in Older Adults?

Abstract: Vision functions other than standard visual acuity may affect day-to-day functioning of older adults. Additional studies of these other aspects of vision and how they can be treated or rehabilitated are needed to determine whether these aspects play a role in strategies for reducing disability in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 23 publications
3
93
1
5
Order By: Relevance
“…Many of these objectively measurable visual functions have found to associate with balance and mobility performance. In community-settings loss in contrast sensitivity RW.ERRORRW.ERROR (Lord and Menz 2000;Tiedemann et al 2005;West et al 2002a;West et al 2002b), stereopsis (Lord and Menz 2000), visual fields (West et al 2002a;Patel et al 2006) as well as visual acuity (West et al 2002b) have been associated with impaired postural control or mobility. However, less is known about interactions between these different types of vision impairment (Dhital et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these objectively measurable visual functions have found to associate with balance and mobility performance. In community-settings loss in contrast sensitivity RW.ERRORRW.ERROR (Lord and Menz 2000;Tiedemann et al 2005;West et al 2002a;West et al 2002b), stereopsis (Lord and Menz 2000), visual fields (West et al 2002a;Patel et al 2006) as well as visual acuity (West et al 2002b) have been associated with impaired postural control or mobility. However, less is known about interactions between these different types of vision impairment (Dhital et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…glaucoma, retinis pigmentosa) or attentional (e.g. reduction in 'useful field of view') impairments (Owsley et al 1995;Geruschat et al 1998;Sekuler et al 2000;West et al 2002;Turano et al 2004;Cedrone et al 2008). Conversely, reliance on peripheral vision may be the only option for people with macular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] West et al 18 reported that if more sophisticated tests of visual function such as contrast sensitivity, glare recovery, and dark acuity tests were used, then up to 60% of elderly subjects assessed with these tests failed them, compared to only 20% of the same cohort who failed standard high-contrast (Snellen) visual acuity tests. Similarly, it is now well recognised that standard clinical tests of a patient's visual field may also underestimate the peripheral visual field problems in this group of patients.…”
Section: Eyementioning
confidence: 99%
“…20,21 Furthermore, visual impairment impacts on a wide range of objective and subjective measures of functional status, including those measures which are not actually vision dependant, such as psychological well being. 16,18,[22][23][24][25] One of the principle aims of the current study was to develop a simple bedside screening test that could be incorporated into the rehabilitation package offered to patients who fall sustaining a fractured neck of femur. While not without its limitations, high-contrast Snellen visual acuity is still deemed to be a useful indicator of the ability of an older patient to perform a range of visiondependant daily living tasks.…”
Section: Eyementioning
confidence: 99%